Downregulation of the Repressor Element 1-Silencing Transcription Factor (REST) Is Associated with Akt-mTOR and Wnt-β-Catenin Signaling in Prion Diseases Models - Song, Zhiqi; Shah, Syed Z. A.; Yang, Wei; Dong, Haodi; Yang, Lifeng; Zhou, Xiangmei; Zhao, Deming (Frontiers in Molecular Neuroscience, 2017)
Prion diseases are a group of infectious diseases characterized by multiple neuropathological changes, yet the mechanisms that preserve function and protect against prion-associated neurodegeneration are still unclear. We previously reported that the repressor element 1-silencing transcription factor (REST) alleviates neurotoxic prion peptide (PrP106-126)-induced toxicity in primary neurons. Here we confirmed the findings of the in vitro model in 263K infected hamsters, an in vivo model of prion diseases and further showed the relationships between REST and related signaling pathways. REST was depleted from the nucleus in prion infected brains and taken up by autophagosomes in the cytoplasm, co-localizing with LC3-II. Importantly, downregulation of the Akt–mTOR and at least partially inactivation of LRP6-Wnt-β-catenin signaling pathways correlated with the decreased levels of REST in vivo in the brain of 263K-infected hamsters and in vitro in PrP106-126-treated primary neurons. Overexpression of REST in primary cortical neurons alleviated PrP106-126 peptide-induced neuronal oxidative stress, mitochondrial damage and partly inhibition of the LRP6-Wnt-β-catenin and Akt–mTOR signaling. Based on our findings, a model of REST-mediated neuroprotection in prion infected animals is proposed, with Akt–mTOR and Wnt-β-catenin signaling as the key pathways. REST-mediated neuronal survival signaling could be explored as a viable therapeutic target for prion diseases and related neurodegenerative diseases.